2011
DOI: 10.1007/s12098-010-0343-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Childhood Injuries in Rural Puducherry, South India

Abstract: There is a need for community based health education intervention for mothers, caregivers, school teacher and capacity building of village level health workers such as ANM and AWW. Health education message should include preventive measures for the leading causes of childhood injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
15
3
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 10 publications
7
15
3
4
Order By: Relevance
“…This finding contradicted with (Eldosoky , 2011) who revealed that more than half of injured children (50.6%) were aged 9 -12 years. Regarding sex differences it was found that more than half of the injured children were boys (58.7%) than girls (41.3%) this result agrees with (Eldosoky , 2011) who found that the incidence rate of home accidents constituted (57.5%) for boys and (42.5%) for girls and also similar to study in Turkey (53.4% for boys and 46.6% for girls) and ( ztürk C et al, 2010 )who and also agreed with (Mahalakshmy et,al , 2011 ) who found that prevalence of injury was high among male children. Differences in regional and sample characteristics may affect the statistical significance of the impact of gender in injuries (Polat S et al, 2005) As regards types of home accidents the present study indicates that Cut/wound represented the highest percentage of home injury (37.3%) and this agrees with ( Abd El-Aty., et al, 2005) who indicated that wounds were the most common accidents among studied children was (37.4%).…”
Section: Discussionsupporting
confidence: 87%
“…This finding contradicted with (Eldosoky , 2011) who revealed that more than half of injured children (50.6%) were aged 9 -12 years. Regarding sex differences it was found that more than half of the injured children were boys (58.7%) than girls (41.3%) this result agrees with (Eldosoky , 2011) who found that the incidence rate of home accidents constituted (57.5%) for boys and (42.5%) for girls and also similar to study in Turkey (53.4% for boys and 46.6% for girls) and ( ztürk C et al, 2010 )who and also agreed with (Mahalakshmy et,al , 2011 ) who found that prevalence of injury was high among male children. Differences in regional and sample characteristics may affect the statistical significance of the impact of gender in injuries (Polat S et al, 2005) As regards types of home accidents the present study indicates that Cut/wound represented the highest percentage of home injury (37.3%) and this agrees with ( Abd El-Aty., et al, 2005) who indicated that wounds were the most common accidents among studied children was (37.4%).…”
Section: Discussionsupporting
confidence: 87%
“…This is similar to the study in Turkey (53.4% and 46.6% respectively), although the difference was not statistically significant in that study [11]. Mahalakshmy et al in India also found that prevalence of injury was significantly higher among male children [14]. Differences in regional and sample characteristics may affect the statistical significance of the impact of gender in injuries [15].…”
Section: Discussionsupporting
confidence: 84%
“…Their higher rate may be due to the younger age group on which the latter study was conducted. On the other hand, our figure was higher than in a rural area in India ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫عرش‬ ‫الثامن‬ ‫املجلد‬ ‫العارش‬ ‫العدد‬ among 1613 children aged < 14 years in which the rate of injuries was 23.0%, with more than half of these occurring at home [12]. This lower figure might be explained by the demographic variations among the Egyptian and Indian populations.…”
Section: Discussioncontrasting
confidence: 60%
“…Similar finding was reported in the WHO study[5] and Mahalakshmy et al . [9] In the present study, boys suffered 70% of all injuries while girls suffered 30%. The prevalence in boys was 8.4% (95% CI: 6.6-10.2) and in girls it was 5.1% (95% CI:3.5-6.7).…”
Section: Discussionmentioning
confidence: 45%